Ontmoetingen 1930-1942 - Rens, Jef (Antwerpen Amsterdam : De Nederlandsche Boekhandel, 1984)
Ontmoetingen met o.m. Marcel Déat, Gust Demuynck, Herman Vos, Corneel Mertens, Joseph Bondas, Emile Vandervelde, Isabelle Blume, Achille van Acker, Hendrik de Man
Nederlands
Monografie
Keywords: Wereldoorlog 2; interbellum; egodocumenten